A ZIF-8@H:ZnO core–shell nanorod arrays/Si heterojunction self-powered photodetector with ultrahigh performance. Issue 17 (11th April 2019) - Guo, Tianchao; Ling, Cuicui; Li, Xiaofang; Qiao, Xurong; Li, Xiao; Yin, Yingying; Xiong, Ya; Zhu, Lei; Yan, Keyou; Xue, Qingzhong
Abstract : The superior performance of the self-powered ZIF-8@H:ZnO core–shell NRs/Si heterojunction can be attributed to the combination of hydrogenation doping and ZIF-8 passivation. Abstract : Native defects can degrade the performance and stability of an optoelectric device. Herein, a zeolitic imidazolate framework-8 (ZIF-8)@H:ZnO core–shell nanorod arrays/Si heterojunction self-powered photodetector is demonstrated. Via the combined process of hydrogenation and ZIF-8 passivation, the photoresponsive characteristics of this photodetector could be significantly enhanced; the photodetector exhibited the superior detectivity of ∼2.14 × 10 16 Jones (1 Jones = 1 cm Hz 1/2 W −1 ), the high responsivity of ∼7.07 × 10 4 mA W −1, the prominent sensitivity of ∼2.08 × 10 12 cm 2 W −1 and broadband photodetection in the region ranging from ultraviolet to near infrared. As a critical figure of merit, its responsivity increased by nearly 5 orders of magnitude than that of the pristine ZnO nanorod arrays/Si heterojunction photodetector. More importantly, the comprehensive performance of the ZIF-8@H:ZnO core–shell nanorod arrays/Si heterojunction photodetector was significantly higher than that of ZnO-based photodetectors reported to date, and it was comparable to those of two-dimensional (2D) materials, zero-dimensional (0D) materials, topological insulators, perovskites and other oxide-based self-powered photodetectors. This novel post-treatment strategy has significant potential for application in the development of high-performance self-powered photodetectors. Moreover, this study may be extended to other oxide-based optoelectronic devices.